Superabsorbent Polymers as a Tool for Sustainable Water Management in Semi-Arid Agriculture: A Case Study from the Upper Cheliff Plain, Algeria - Taibi, Hamida; Bouderbala, Abdelkader (Annals of Arid Zone, 2025)
Water scarcity presents a significant challenge to agriculture in Mediterranean regions, where semi-arid climates, irregular rainfall, and increasing water demand threaten crop productivity. Superabsorbent polymers (SAPs), or hydrogels, offer a promising solution by enhancing soil water retention and improving irrigation efficiency. This study evaluates the effect of potassium polyacrylate hydrogel on soil properties in Algeria’s Upper Cheliff plain, a semi-arid area experiencing declining rainfall and rising temperatures. A randomized block experiment was conducted to assess five hydrogel application rates (0 to 4 g per plant-1) under drip irrigation. Key soil parameters-moisture content, pH, temperature, and electrical conductivity (EC)-were monitored throughout the duration of the experiment. Results indicated that moderate hydrogel doses (1.75 to 2 g per plant-1) significantly increased soil water retention (up to 34.9%, compared to 27.93% in control plots). These doses also caused slight reductions in soil pH and helped stabilize soil temperature. Conversely, higher application rates yielded diminishing benefits and led to increased EC levels, suggesting a potential risk of soil salinity. Statistical analysis confirmed that treatment effects were significant (p